Building Supply Chain Resilience During Global Geopolitical Disruptions In The Manufacturing Sector : A Comparative Analysis Between Bangladesh and Finland - Sultana, Jarin (My University, 2026)
Abstract: The global manufacturing supply chains have been exposed to more vulnerabilities to geopolitical disruptors such as the trade conflicts, pandemics, and political instabilities. These shocks have revealed certain major vulnerabilities in traditional supply chain models with a focus on efficiency rather than resilience. This has led to the emergence of the supply chain resilience as a vital ability in ensuring a continuity in operations and performance. The research problem is to investigate how manufacturing supply chains resilience to geopolitical disruptions, with the ability to respond to such disruptions, and the impact this capacity has on operational performance. A comparative approach is taken, whereby Bangladesh is considered a developing economy and Finland is a developed economy with well developed industrial systems. The research design used is a quantitative and comparative secondary research design. The data is gathered using credible sources including the World Bank, UNCTADstat as well as company reports and industry publications. Major indicators, such as trade performance, manufacturing output, and supply chain diversification are examined. The SAS Enterprise Guide and SAS Studio is used to process the data, and descriptive statistics, trend analysis, and comparative analysis methods are used to analyze the difference between the two countries. The results will be deemed to show that the resilience capabilities of supply chain in the form of diversification, digitalization, and risk management practices positively affect the performance of operations. Finland can be more resilient since there is better infrastructure and a greater technological adoption rate, whereas Bangladesh can be vulnerable regarding a lack of digital integration and reliance on the global supply networks. Nonetheless, other adaptive strategies that Bangladesh can exhibit include flexible sourcing and cost efficiency. The research is both theoretical and practical because it offers information on the ways in which resilience strategies vary in terms of economic backgrounds. It emphasizes the significance of digital transformation and strategic flexibility in boosting supply chain resilience. The comparative study between Bangladesh and Finland covers a significant research gap and helps to create more resiliency in manufacturing supply chains.
Keywords: supply chains; resilience; COVID-19; manufacturing; pandemics; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management